Sliding behaviour and surface quality after static air polishing of conventional and modern bracket materials: in vitro analysis - Hodecker, Lutz; Bourauel, Christoph; Braumann, Bert; Kruse, Teresa; Christ, Hildegard; Scharf, Sven (Journal of orofacial orthopedics, 2023)
As part of orthodontic treatment, air polishing is routinely used for professional tooth cleaning. Thus, we investigated the effects of static powder polishing on sliding behaviour and surface quality of three different bracket materials (polymer, ceramic, metal), including a 3D-printed bracket.